Fundamental mode shape-based normalization scheme for damage detection of minarets: A non-model-based approach. (May 2023) - Nguyen, Quy Thue; Livaoğlu, Ramazan
Highlights: Simple sensor network containing a modest quantity of accelerometers is erected along with the height of monitored minarets. A quick and robust normalization scheme is proposed to detect typical failure scenarios of slender masonry minarets. The normalizing point is located from low to high positions to figure out the changes in the fundamental mode shape. Reliable damage detection is attained as long as the modal data is noise-free or reasonable-level noise-contaminated. Abstract: Historical, cultural, and artistic masonry structures like minarets constructed in regions prone to dynamic effects such as strong winds and earthquakes are vulnerable as a consequence of their slenderness and brittle materials. Structural health monitoring (SHM) has not been employed adequately in the regular control of minarets' integrity for early warning of disaster. Meanwhile, the protection and preservation of such a cultural inheritance are acute. A non-model-based normalization scheme is proposed to detect damage in minarets based only on the changes in terms of the fundamental mode shape generated by a modest quantity of accelerometers. The backbone idea lies in the similarities in terms of the fundamental mode shape between slender minarets and beam-like structures. Particularly, the modal amplitudes below a specific normalizing node change significantly if damage occurs below this point. Thereby, moving upward the location of this point straightforwardly leads to damage detection of minarets. The proposed technique is implemented on Hacılar mosque's minaret (24.25 m high) built in 1467 in Bursa city, Türkiye. Reliable damage prediction is attained as long as the modal information is noise-free or reasonable-level noise-polluted.